Possible explanations for the transformation of the Northern Great Plain Region's labour market - Gerda, István Zsolt (Acta Agraria Debreceniensis, 2009)
As a result of the processes of hungarian economy and society the increase in territorial differences is noticeable in the last few days. The changes in society's status, the rate of increase and the level of development can be tracked for example in the diverse variation of labour market. In my study I would like to demonstrate the typical processes of labour market based on the time scale between 2000-2007, and I also want to reveal the root causes of the change in unemployment rate. The source of data is a regular, representative labour-survey by the Hungarian CentralStatistical Office based on interviewing people, as well as registration on place-hunters by the Employment and Social Office together with the summary of governmental subsidy. I targeted the age-groups between 15-74 years in my analysis, but the results are not modified by the over 65 years old population because of their small economical importance. I define the status of labour market by markers among others like economical activity, employment rate, unemployment rate, and I also consider the change in the amount of registered place-hunters in the period examined. My aim is to determine the responsible coefficients of the change in unemployment rate.